Potential of antimicrobial volatile organic compounds to control Sclerotinia sclerotiorum in bean seeds - Fialho, Maurício Batista; de Moraes, Maria Heloisa Duarte; Tremocoldi, Annelise Roberta; Pascholati, Sérgio Florentino (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the potential of an artificial mixture of volatile organic compounds (VOCs), produced by Saccharomyces cerevisiae, to control Sclerotinia sclerotiorum in vitro and in bean seeds. The phytopathogenic fungus was exposed, in polystyrene plates, to an artificial atmosphere containing a mixture of six VOCs formed by alcohols (ethanol, 3‑methyl‑1‑butanol, 2‑methyl‑1‑butanol and phenylethyl alcohol) and esters (ethyl acetate and ethyl octanoate), in the proportions found in the atmosphere naturally  produced  by  yeast. Bean seeds  artificially  contamined with the  pathogen were fumigated with the mixture of VOCs in sealed glass flasks for four and seven days. In the in vitro assays, the compounds 2‑methyl‑1‑butanol and 3‑methyl‑1‑butanol were the most active against S. sclerotiorum, completely inhibiting its mycelial growth at 0.8 µL mL-1, followed by the ethyl acetate, at 1.2 µL mL-1. Bean seeds fumigated with the VOCs at 3.5 µL mL-1 showed a 75% reduction in S. sclerotiorum incidence after four days of fumigation. The VOCs produced by S. cerevisiae have potential to control the pathogen in stored seeds.
Keywords: Phaseolus vulgaris; alternative control; fumigation; white mold; yeast